Innovative Technological Solutions for Environmental Sustainability in Chinese Engineering Practices - Din, Azhar Ud; Yang, Yang; Khan, Muhammad Inam Makki; Khuram, Waqas (Engineering, Technology & Applied Science Research, 2024)
The Chinese government announced the clear goal of attaining carbon neutrality by 2060, in order to gradually achieve net-zero carbon dioxide (CO2) emissions, whose impact on global warming needs to be reduced while also a sustainable industry needs to be promoted. Recognizing the critical role of Green Human Resource Management (GHRM) in supporting green innovation and achieving the carbon neutrality agenda, this study aims to fill a research gap by emphasizing this overlooked nexus. The former examines the influence of GHRM, green innovation, and carbon neutrality on environmental performance by carefully analyzing the current literature on China’s achievement of carbon neutrality and its implications for environmentally friendly performances. The current study assesses the planning frameworks of the country, explores the concept of achieving carbon neutrality, and evaluates the practical implications.